2022 8th International Conference on Automation, Robotics and Applications (ICARA) 2022
DOI: 10.1109/icara55094.2022.9738519
|View full text |Cite
|
Sign up to set email alerts
|

LiDAR Ground Segmentation and Modeling for Mobile Robots in Unstructured Terrain

Abstract: We propose a new method for fine registering multiple point clouds simultaneously. The approach is characterized by being dense, therefore point clouds are not reduced to pre-selected features in advance. Furthermore, the approach is robust against small overlaps and dynamic objects, since no direct correspondences are assumed between point clouds. Instead, all points are merged into a global point cloud, whose scattering is then iteratively reduced. This is achieved by dividing the global point cloud into uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Figure 5b) provides a relatively sparse but precise representation of the environment. With DMSA SLAM (Skuddis and Haala, 2024) we were able to successfully process the data from the LiDAR sensor together with the IMU data after a few adaptations to the initially published pipeline/parameters. The alignment of the environment representation created on the basis of Visual SLAM showed that the resulting map was down-scaled by approximately 5% compared to the reference.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Figure 5b) provides a relatively sparse but precise representation of the environment. With DMSA SLAM (Skuddis and Haala, 2024) we were able to successfully process the data from the LiDAR sensor together with the IMU data after a few adaptations to the initially published pipeline/parameters. The alignment of the environment representation created on the basis of Visual SLAM showed that the resulting map was down-scaled by approximately 5% compared to the reference.…”
Section: Resultsmentioning
confidence: 99%
“…Newer approaches also include mechanisms such as Scan Context (Kim and Kim, 2018) or LoGG3D-Net (Vidanapathirana et al, 2022) to detect the revisiting of already mapped locations (loop closures) and to improve consistency through pose graph optimization (Behley and Stachniss, 2018), (Ramezani et al, 2022). In some modern methods, the points are still reduced to edge and planar features during preprocessing (Shan et al, 2020), while in others the points are combined into disk-like surface elements (Behley and Stachniss, 2018), (Ramezani et al, 2022) or in so-called dense approaches simply (downsampled) points are used (Dellenbach et al, 2022), (Xu et al, 2022), (Vizzo et al, 2023), (Skuddis and Haala, 2024). In modern LiDAR SLAM systems IMU data are used to increase robustness in situations with fast movements and to reduce the orientational drift through gravity estimations (Ramezani et al, 2022), (Shan et al, 2020), (Xu et al, 2022), (Skuddis and Haala, 2024).…”
Section: Lidar Slammentioning
confidence: 99%
See 3 more Smart Citations